Online corporate reputation: A panel data approach and a reputation index proposal applied to the banking sector - Ramos, Celia M. Q. (2021)
Managing an online corporate reputation (OCR) is increasingly strategic to improving the corporation's eco-nomic performance. What becomes crucial is to collect, process and analyse the comments expressed in the online medium, considering them as an intangible asset with an impact on tangible assets and consequences on business value. This research contributes to show the potential of the big-data environment, enhanced by the use of business intelligence tools and combined with panel econometric models. This is complemented by the elaboration of an Online Corporate Reputation Index (OCRI) to measure the economic corporate performance. The findings show that after applying the conceptual model to the banking sector, the experience associated with ethics is the intangible asset that has the most impact on the economic performance associated with each bank. In addition, the definition of an index helps to position one company in relation to another and to an entire economic sector.